2018
DOI: 10.1097/prs.0000000000004939
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Experience Using a New Robotic System Created for Microsurgery

Abstract: It is feasible to complete anastomotic microsurgery on silicone vessels using the MicroSure robotic system. In comparison with the conventional method, time to perform the anastomosis was longer and quality of microsurgical skills was lower in the robot-assisted group. However, the robot-assisted performance showed steeper learning curves for both surgical time and domains of microsurgical skills. The encouraging results indicate further development of the system and (pre)clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 23 publications
6
36
1
8
Order By: Relevance
“…This matter will certainly be discussed in future larger studies. The aforementioned finding regarding SAMS scores is in line with previous preclinical experiments 6 . It might be suggested that the use of SAMS is less appropriate for assessing robot-assisted microsurgical procedures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This matter will certainly be discussed in future larger studies. The aforementioned finding regarding SAMS scores is in line with previous preclinical experiments 6 . It might be suggested that the use of SAMS is less appropriate for assessing robot-assisted microsurgical procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Microsurgical platform. The MUSA has been evaluated in preclinical tests of the system 6,7 . In general, the system is composed of (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed description of the Gen‐1 MSR is provided in a recent publication in Plastic and Reconstructive Surgery . In the aforementioned report, the feasibility of performing microvascular anastomosis using the MSR on silicone vessels has been confirmed.…”
Section: A New Master‐slave Platform For (Super) Microsurgerymentioning
confidence: 86%
“…In a previous study on silicone vessels comparing robotic‐assisted anastomoses to the conventional technique, it was shown that completing microvascular anastomosis using the MSR was feasible but required significantly more time. Nevertheless, in the robotic‐assisted group, a rapid decline in anastomosis time and improvement of the quality of the anastomosis was found …”
Section: Discussionmentioning
confidence: 98%